Efecto del manejo fisionutricional sobre el rendimiento de mazorcas y forrajero de la variedad de maíz INIAP 543-QPM - Rivera Palma, Ivone Katherine (2023)
The objective of the research was to evaluate the effect of physionutritional management on the yield of cob and forage of the INIAP 543-QPM variety. The work was carried out during the dry season of 2021, in two towns in Manabí province, which were El Frutillo in Rocafuerte canton, and Figueroa in Bolívar canton. The treatments evaluated were Physionutritional Management (PM), and Conventional Management (CM). The PM consisted of the combined application of mineral fertilizers and biostimulants, while the CM consisted of the application of only mineral fertilizers. The main variables recorded were the yield of commercial cob in bushels (bundles of 150 cob), forage biomass yield (40 kg silage bags) and economic profitability (USD ha-1). The data were analyzed with the Student's t test (α = 0.05) for paired observations. The results showed that the PM increased significantly (p<0.05) the production of commercial cob and silage in both evaluated locations, with respect to the CM. The economic profitability was 146 and 148% for the PM, in Rocafuerte and Bolívar, in relation to the CM that reached an economic profitability of 133 and 118%, for both locations, respectively. The PM is postulated as an effective technological alternative to increase the productivity and profitability of the INIAP 543-QPM maize variety in Manabí.